KEPASTIAN HUKUM PEMEGANG HAK ATAS TANAH DI KAWASAN HUTAN (ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 45/PUU-IX/ 2011 DIHUBUNGKAN DENGAN PUTUSAN MAHKAMAH AGUNG NOMOR 47 P/HUM/2011) - ENNI SYARIFAH HARAHAP (PREMISE LAW JURNAL, 2015)
The result of the research showed that the Ruling of the Constitutional Court No.45/2011 has judicially reinforced legal certainty for the people entitled to the land rights in the forest area, but it is factually not implemented yet. The Rulling of the Supreme Court No. 47/2011 has also judicially provided legal certainty for the people entitled to the land rights in the forest area, especially in Nort Sumatera. However, the Decree of the Minister of Forestry does not factually accommodate the interest of the people entitled to the land rights. In other words the Decree actually has not yet provided legal certainty for the people entitled to the land rights in the forest area. Keywords: Legal Certainty, Judicial Review, Forestry Law